Measurement Of Athletic Physical Tests Of Shot Put Numbers On SMP Negeri 2 Indralaya Utara Students Using Outdoor Laboratories At The Education Park - Maryani Maryani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The research entitled the measurement of athletic physical tests of shot put numbers on students of SMP Negeri 2 Indralaya Utara using outdoor laboratories in educational parks. Sports are very important in our lives, therefore it is very necessary to do physical tests in improving physical fitness.Measurement of physical tests is the process of collecting data from the measurement process. The purpose of this study is to determine the physical level. This research is a quantitative study with the design of research subjects of SMP Negeri 2 Indralaya Utara students with a total of 30 students consisting of 20 boys and 10 girls. Data collection using tests, with the instruments used as follows: endurance test using bleep test, speed test using 40 meter run, arm muscle strength using push up test, abdominal muscle strength using 30 second sit up test, leg muscle explosiveness using vertical jump test. The research was conducted in the outdoor laboratory of the education park. For data analysis techniques using descriptive analysis, which is expressed in percentage form. The results of the five tests were obtained in the sufficient category and there were 3 players (10%) in the excellent category, 5 players (20%) in the good category, 12 players (37%) in the sufficient category, 9 players (30%) in the less category, 1 player (3%) in the very poor category. It can be concluded that the physical test of athletics in the shot put number of SMP Negeri 2 Indralaya Utara is in the sufficient category. After this research is carried out, it is hoped that awareness for coaches and students can increase and maintain physical activity so that they have good physical quality.